Presidents Abroad: The Politics of Personal Diplomacy. (December 2019) - Ostrander, Ian; Rider, Toby J.
A president's most precious commodity is time, and nowhere is this scarcity more apparent than with respect to international travel. Personal presidential involvement in diplomatic relations has proven to yield significant benefits, and yet traveling to engage in face-to-face diplomacy is often prohibitively expensive for American executives in time and attention. Given such restrictions, when and where do presidents choose to travel? We use a data set of more than 750 presidential trips spanning more than one hundred countries and a century of history to investigate the domestic and international factors influencing when, where, and for what reason presidents are likely to travel abroad. We provide a detailed examination of presidential travel over time and find that domestic political contexts influence presidential propensities to travel consistent with expectations based on allocating time and attention as limited resources.